Livelihood Diversification as Political Translation - Sudirman (PCD Journal, 2021)
This article questions the ability of the resistance framework to explain local communities' political reactions to oil palm expansion. Guided by a translation and ethnographic framework, this study investigates the Modang Dayak community's political reaction from below to large-scale land acquisitions in upland East Kalimantan. It shows that, based on their knowledge and everyday life practice, the Modang Dayaks have the agency to negotiate the land scarcity that has accompanied oil palm expansion. This study contributes to reaction theory by arguing that livelihood diversification is a form of political translation used to negotiate the difficulties created by palm oil; as land has become increasingly scarce, the Modang Dayaks have redefined their relationship with it. This reality tends to be ignored in political science debates because researchers generally view political reactions through a resistance paradigm. Ultimately, however, the politics of translation go beyond the politics of resistance.